What Dynamic Managerial Capabilities Are Needed for Greater Strategic Alliance Performance? - Andrejs Čirjevskis (Journal of Open Innovation: Technology, Market and Complexity, 2019)
Despite the rising interest in the nature of open innovation and its implications for greater strategic alliance performance, limited attention has been paid to what the dynamic managerial capabilities underpinning those processes are. Moreover, only limited research has examined how open innovation is practiced by firms working within various network forms (ecosystems, platforms, and strategic alliances) and what dynamic managerial capabilities ensure such networks’ collaborations. We need to further develop the concept of the coupled (collaborative) type of open innovation and to show how open innovation mechanisms, such as strategic alliances, are underpinned by dynamic managerial capabilities and to understand what their “micro-foundations” are. Thus, the goal of this article is to understand the role of sub-capabilities (how managers think and decide) of dynamic managerial capabilities as drivers of successful alliance performance.